Foreign Direct Investment (FDI) and Natural Resources: Blessing or Curse? Empirical Evidence from the Gulf Cooperation Council (GCC) - Elheddad, Mohamed; Thapa-Parajuli, Resham; Alharthi, Majed (Journal of Reviews on Global Economics, 2020)
This paper investigates why foreign direct investment (FDI) inflows are disproportionate among resource and non-resource sectors in oil-rich countries over the period 1980-2017. We constructed a balanced panel of data for Gulf Cooperation Council (GCC) countries from the database of the United Nations Conference on Trade and Development (UNCTAD) and disaggregate data from The Financial Times. We regress total and sectoral FDI inflows on oil rents to a GDP ratio, controlling other socio-economic variables. Our results first consider oil rents. This proxy for natural resources is negatively associated with total FDI inflows. The oil rents/GDP share and resource-based FDI have a significantly positive correlation. However, the adverse effect of oil rents remains true in the case of the non-resource sector foreign investment. Second, oil price fluctuations lead to a rise in the non-resource FDI but discourage resource-related FDI inflows. These empirical results confirm that FDI-Natural resources curse through the crowd-out effect of natural resources in the Gulf Cooperation Council (GCC) countries. Our results are robust to different panel data estimators.